EFFECTIVE LEADER STRATEGIES IN LEADING AND MANAGING A COMPANY - Zulriansyah Nur; Asrindah Nst; Muya Syaroh Iwanda Lubis; Buyung Solihin Hasugian (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2022)
ABSTRACTEffective leadership is something which enables other people to behave as if they were the leader and thus convinces them that this is the way to satisfy their needs. Leadership is a quality that any organization's leader must possess. The effectiveness of one of the leaders can be seen from the ability to influence and raise the group. The purpose of this study is to quantify the importance of effective homosexual leadership inside a certain organization in order to determine if it will elevate and elevate its members. based on to the results of this study, effective leadership is defined as leadership that is tailored to the circumstances and conditions of the people in charge. The function of the leadership is determined by the kind of leadership that may give the person who is being pegged the opportunity to engage in activity as well as to record and carry out complaints. This means that each creative or innovative idea inside a successful system must be realized and put to use.Keywords: Leadership Style, Morale, Leader Influence